The area of focus education to the future elite in the modern conditions - Reznichenko, О. (Problems of Engineer-Pedagogical Education, 2018)
The article deals with the formation of public position for future elite of the nation based on the concept of the state program of work with gifted youth in the XXI century modern conditions of Ukraine. The evolution of work in the second half of the twentieth century was researched. Determined that feature training future professionals anchylosis engineering industry is the high level of nervous and mental tension, as 70-90% of teaching time they are forced into a sedentary position - sitting, preferably on a computer, which increases the burden on the organs of vision and nervous system and, crucially, the level of health. These facts must be considered during extracurricular educational work. The study found that one of the priorities of educational work in VTNZ is working to educate the professional leaders. It is shown that the Sami school as an integral structural component of open social and educational system has become the focus, to create the conditions and the objectives on forming a new generation of professional.